Drivers influencing the end price of fuel in the Czech Republic and implications for relevant businesses - Fingl, Filip (2014)
This thesis deals with understanding drivers influencing the end price of fuel in the Czech Republic and ramifications for relevant companies. Its aim is to provide a comprehensive understanding of all relevant elements have been influencing end prices of gasoline and diesel during last 8 years, understand their leverage and uncover which of those were the most important for this development. These are then researched using mainly graphical analysis and basic statistical tools. The delivery is that both prices of gasoline and diesel are highly correlated with the price development of crude oil and the prices of their respective commoditized barges expressed in the nominal value of CZK. It was also discovered that there are visible tendencies for asymmetrical pricing reaction and reaction lags, which could serve as a basis for a follow-up work. Based on these findings several conclusive recommendations for relevant companies were built and delivered.